Intelligent virtual rehabilitation system for the elderly with memory deficits - Guo, Wenhua (2008)
The application of virtual reality (VR) technology in rehabilitation has significant advantages over the conventional rehabilitation methods. However, VR applications for the dementia patients are few and in their earliest stage. A number of problems need to be studied and clarified. This project has developed a new memory rehabilitation methodology for the dementia elderly. The methodology explores the conventional memory rehabilitation theory and approaches, the advanced virtual reality (VR) technology, and fuzzy logic theory to develop an intelligent approach. To study the proposed methodology, this project has developed a methodology for building the virtual environment suitable for the dementia patients with memory deficits. This project has also developed a method to capture the therapist’s knowledge and experience to establish a fuzzy-based Intelligent Assistant for assisting the patient training in the virtual environment. Test results fiom the therapists, healthy old persons, and patients proved the effectiveness of the methodology for building virtual environment and the knowledge acquisition method.